2022
DOI: 10.3390/genes13040609
|View full text |Cite
|
Sign up to set email alerts
|

SNPs in Genes Related to DNA Damage Repair in Mycobacterium Tuberculosis: Their Association with Type 2 Diabetes Mellitus and Drug Resistance

Abstract: Genes related to DNA damage repair in Mycobacterium tuberculosis are critical for survival and genomic diversification. The aim of this study is to compare the presence of SNPs in genes related to DNA damage repair in sensitive and drug-resistant M. tuberculosis genomes isolated from patients with and without type 2 diabetes mellitus (T2DM). We collected 399 M. tuberculosis L4 genomes from several public repositories; 224 genomes belonging to hosts without T2DM, of which 123 (54.9%) had drug sensitive tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Although none of the SNPs with low allele frequency showed significant associations with DR, the allelic variation in MutY (4030721, Ala 77Pro) and RuvB (2923293, Arg314Pro) present in different sublineages could suggest a homoplasy event. Although RuvB is a protein involved in the resolution of branched DNA structures [ 34 ], our previous observations suggest that the occurrence of SNPs in RuvB is more frequent in the presence of DMT2 in the host [ 35 ]. On the other hand, recent research has shown that some mutations in MutY abrogate its functions generating a hypermutagenic phenotype, with increased survival and rapid acquisition of resistance mutations for rifampicin and ciprofloxacin [ 12 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the SNPs with low allele frequency showed significant associations with DR, the allelic variation in MutY (4030721, Ala 77Pro) and RuvB (2923293, Arg314Pro) present in different sublineages could suggest a homoplasy event. Although RuvB is a protein involved in the resolution of branched DNA structures [ 34 ], our previous observations suggest that the occurrence of SNPs in RuvB is more frequent in the presence of DMT2 in the host [ 35 ]. On the other hand, recent research has shown that some mutations in MutY abrogate its functions generating a hypermutagenic phenotype, with increased survival and rapid acquisition of resistance mutations for rifampicin and ciprofloxacin [ 12 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another significant tool could be the use of Mendelian randomization (MR), which is a highly efficient method that allows researchers to identify a causal relationship between phenotypes (diseases) and estimates of causal effects, thus overcoming the limitations of observational studies [45]. To perform such an analysis and to establish a possible connection between sarcopenia and TB, a list of DNA polymorphisms, known as single-nucleotide polymorphisms (SNPs), which are associated with these diseases could be utilized and investigated [46,47]. As a result, in order to further clarify the association between the entities of TB infection and sarcopenia in the future, it may be appropriate to carry out MR using previously known genetic tools.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the SNPs with low allele frequency showed significant associations with DR, the allelic variation in MutY (4030721, Ala 77Pro) and RuvB (2923293, Arg314Pro) present in different sublineages could suggest a homoplasy event. Although RuvB is a protein involved in the resolution of branched DNA structures[32], our previous observations suggest that the occurrence of SNPs in RuvB is more frequent in the presence of DMT2 in the host [33]. On the other hand, recent research has shown that some mutations in MutY abrogate its functions generating a hypermutagenic phenotype, with increased survival and rapid acquisition of resistance mutations for rifampicin and ciprofloxacin [11,34].…”
Section: Discussionmentioning
confidence: 99%